Amplification of human papillomavirus genomes in vitro is dependent on epithelial differentiation. - Bedell, M A (1991)
Human papillomaviruses (HPVs) infect squamous epithelium and establish their genomes as episomes in proliferating basal cells. As infected cells differentiate, the viral DNA is amplified to high copy number and infectious virus is produced. Viral production has not yet been observed in vitro due to the inability of standard culture methods to duplicate most stages of epithelial differentiation. In this study, we have examined a cell line derived from a low-grade cervical lesion and found that it contained episomal copies of an HPV-31 subtype, HPV-31b, at approximately 50 copies per cell. When allowed to stratify at the air-liquid interface of in vitro raft cultures, this cell line differentiates in a manner which histologically resembles a low-grade cervical lesion in vivo. We have observed the amplification of HPV-31b genomes in distinct foci in the upper portion of the in vitro-stratified epithelium similar to that found in productive HPV infections in vivo. Although transcripts from the late region of HPV-31b were also detected specifically in stratified raft cultures, no capsid protein was found. These studies duplicate one important aspect of a productive HPV infection in vitro, the differentiation-dependent amplification of papillomavirus genomes.